2008
DOI: 10.1007/s00330-008-1253-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, intraindividual comparison of MRI versus MDCT for endoleak detection after endovascular repair of abdominal aortic aneurysms

Abstract: This study compares MRI and MDCT for endoleak detection after endovascular repair of abdominal aortic aneurysms (EVAR). Forty-three patients with previous EVAR underwent both MRI (2D T1-FFE unenhanced and contrast-enhanced; 3D triphasic contrast-enhanced) and 16-slice MDCT (unenhanced and biphasic contrast-enhanced) within 1 week of each other for endoleak detection. MRI was performed by using a high-relaxivity contrast medium (gadobenate dimeglumine, MultiHance). Two blinded, independent observers evaluated M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…45 MR imaging, especially delayed imaging with gadolinium or blood-pool contrast enhancement, has been reported to be particularly sensitive and useful as a means of detecting endoleak. 46,47 The sensitivity and specificity of available imaging methods for endoleak detection have not been characterized well, in part because some stent grafts are not MR-compatible. Dynamic CT or dynamic MR can quantify aneurysm morphology over time, and have been suggested as another means to evaluate for potential sac pressurization.…”
Section: Endoleakmentioning
confidence: 99%
“…45 MR imaging, especially delayed imaging with gadolinium or blood-pool contrast enhancement, has been reported to be particularly sensitive and useful as a means of detecting endoleak. 46,47 The sensitivity and specificity of available imaging methods for endoleak detection have not been characterized well, in part because some stent grafts are not MR-compatible. Dynamic CT or dynamic MR can quantify aneurysm morphology over time, and have been suggested as another means to evaluate for potential sac pressurization.…”
Section: Endoleakmentioning
confidence: 99%
“…10 As this contrast agent is available exclusively in the USA, the aim of the present study was to investigate the value of another albumin binding contrast agent. The contrast agent used in the present study, gadobenate dimeglumine, was previously used for endoleak detection by Alerci et al 9 The study by Alerci et al showed that MRI with this albumin binding contrast agent was superior to CTA for endoleak detection, mainly for type II endoleaks. 9 In contrast to Alerci et al, 9 who analyzed a series of patients under follow up after EVAR, the present study investigated a different study population by including only patients with aneurysm growth after EVAR.…”
Section: Discussionmentioning
confidence: 97%
“…The contrast agent used in the present study, gadobenate dimeglumine, was previously used for endoleak detection by Alerci et al 9 The study by Alerci et al showed that MRI with this albumin binding contrast agent was superior to CTA for endoleak detection, mainly for type II endoleaks. 9 In contrast to Alerci et al, 9 who analyzed a series of patients under follow up after EVAR, the present study investigated a different study population by including only patients with aneurysm growth after EVAR. This inclusion criterion was chosen as a detected endoleak could have consequences for treatment strategy, according to the guidelines as stated earlier, only for this group of patients.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, gadoliniumenhanced magnetic resonance (MR) imaging has been reported to be more sensitive to detect endoleaks than contrastenhanced CT in three previous prospective comparative studies [8][9][10]. However, since an association between gadolinium and nephrogenic systemic fibrosis has been demonstrated [11], gadolinium is recommended to be contraindicated or used with caution in patients with renal impairment [12].…”
Section: Introductionmentioning
confidence: 92%